Inflammation, bioactive lipids and atherosclerosis: potential roles of a lipoprotein-associated phospholipase A2, platelet activating factor-acetylhydrolase - Tselepis, Alexandros D; John Chapman, M (Atherosclerosis. Supplements, 2002)
It is well established that inflammation is an integral feature of atherosclerosis and of the cardiovascular diseases which it underlies. Oxidative stress is also recognized as a key actor in atherogenesis, in which it is closely associated with the inflammatory response and bioactive lipid formation. Several bioactive lipids have been identified in the atherosclerotic plaque, including the potent inflammatory mediator platelet activating factor (PAF), PAF-like lipids, oxidised phospholipids (oxPL) and lysophosphatidylcholine (lyso-PC). Recent evidence has established a central role of two phospholipases (PL) in atherogenesis, the non-pancreatic Type II secretory phospholipase A 2 (sPLA 2) and the lipoprotein-associated PLA 2—alternatively termed as PAF-acetylhydrolase (PAF-AH). sPLA 2 is calcium-dependent and hydrolyses the sn-2 acyl group of glycerophospholipids of lipoproteins and cell membranes to produce lyso-PC and free fatty acids. It is also implicated in isoprostane production from oxPL. sPLA 2 is an acute phase reactant, which is upregulated by inflammatory cytokines and may represent a new independent risk factor for coronary heart disease. In contrast to sPLA 2, PAF-AH is calcium-independent and is specific for short acyl groups at the sn-2 position of the phospholipid substrate and with the exception of PAF, can equally hydrolyze oxPL to generate lyso-PC and oxidized fatty acids. Thus PAF-AH plays a key role in the degradation of proinflammatory oxPL and in the generation of lyso-PC and oxidized fatty acids. PAF-AH equally can also hydrolyze short-chain diacylglycerols, triacylglycerols, and acetylated alkanols, and displays a PLA 1 activity. Whereas sPLA 2 may represent a new independent risk factor for coronary artery disease, the potential relevance of PAF-AH to atherosclerosis remains the subject of debate, and recent results suggest that the potential role of the LDL-associated PAF-AH in atherogenesis may be distinct to that of the HDL-associated enzyme. This review is focused on the main structural and catalytic features of plasma PAF-AH, on the association of the enzyme with distinct lipoprotein particle subspecies, on its cellular sources, and finally on the potential significance of this lipoprotein-associated PLA 2 in cardiovascular disease.